Combining transcranial ultrasound with intelligent communication methods to enhance the remote assessment and management of stroke patients: Framework for a technology demonstrator. (September 2016) - Mort, Alasdair; Eadie, Leila; Regan, Luke; Macaden, Ashish; Heaney, David; Bouamrane, Matt-Mouley; Rushworth, Gordon; Wilson, Philip
With over 150, 000 strokes in the United Kingdom every year, and more than 1 million living survivors, stroke is the third most common cause of death and the leading cause of severe physical disability among adults. A major challenge in administering timely treatment is determining whether the stroke is due to vascular blockage (ischaemic) or haemorrhage. For patients with ischaemic stroke, thrombolysis (i.e. pharmacological 'clot-busting') can improve outcomes when delivered swiftly after onset, and current National Health Service Quality Improvement Scotland guidelines are for thrombolytic therapy to be provided to at least 80 per cent of eligible patients within 60 min of arrival at hospital. Thrombolysis in haemorrhagic stroke could severely compound the brain damage, so administration of thrombolytic therapy currently requires near-immediate care in a hospital, rapid consultation with a physician and access to imaging services (X-ray computed tomography or magnetic resonance imaging) and intensive care services. This is near impossible in remote and rural areas, and stroke mortality rates in Scotland are 50 per cent higher than in London. We here describe our current project developing a technology demonstrator with ultrasound imaging linked to an intelligent, multi-channel communication device − connecting to multiple 2G/3G/4G networks and/or satellites − in order to stream live ultrasound images, video and two-way audio streams to hospital-based specialists who can guide and advise ambulance clinicians regarding diagnosis. With portable ultrasound machines located in ambulances or general practices, use of such technology is not confined to stroke, although this is our current focus. Ultrasound assessment is useful in many other immediate care situations, suggesting potential wider applicability for this remote support system. Although our research programme is driven by rural need, the ideas are potentially applicable to urban areas where access to imaging and definitive treatment can be restricted by a range of operational factors.